Pushing the envelope: LPS modifications and their consequences - Simpson, Brent W. (Nat Rev Microbiol, 2019)
The defining feature of the Gram-negative cell envelope is the presence of two cellular membranes with the specialized glycolipid lipopolysaccharide (LPS) exclusively found on the surface of the outer membrane. The surface layer of LPS contributes to the stringent permeability properties of the outer membrane which is particularly resistant to permeation of many toxic compounds, including antibiotics. As a common surface antigen, host immune cells recognize LPS and mount defenses to clear pathogenic organisms. To alter properties of the outer membrane or evade the host immune response, Gram-negative bacteria employ a wide variety of chemical modifications to alter LPS. Here we review key features and physiological consequences of LPS biogenesis and modifications.